Testing Extracts of Pigpea Seeds (Tephrosia vogelii) Against Fall Armyworm (Spodoptera frugiperda) in the Laboratory - Ilham Maulana Siregar; Asmanizar; Sulaiman Ginting; Fenty Maimunah Simbolon (CV. Media Digital Publikasi Indonesia, 2025)
One of the invasive pests that target corn plants is the armyworm Spodoptera frugiperda. This pest can cause damage to every area of the corn plant. Botanical insecticides can be used to control S. frugiperda since it is better for the environment. Rotenone found in the T. vogelii is toxic to insects. The purpose of this study was to assess the effect of the botanical pesticide T. vogelii seed extract mortality of S. frugiperda. T. vogelii seed extract was produced by using a Soxhlet extractor. The tests were conducted using contact poison and stomach poison methods, with the concentrations of the extract solution tested being 0.0625, 0.125, 0.25, and 0.5%. T. vogelii seed extract demonstrated the highest mortality value against S. frugiperda, which is 100% at a concentration of 0.5% in both the contact poison and stomach poison methods. T. vogelii seed extract shows strong toxicity with LC50 = 0.221% and the shortest mortality at 0.5% concentration with LT50 = 2.214 days against S. frugiperda, with an LC50 of 0.316% and the fastest mortality at 0.5% concentration, with an LT50 of 2.457 days. Further research is needed to determine the effect of T. vogelii seed extracts both in the screen house and in the field